2011
DOI: 10.1111/j.1551-2916.2011.04419.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodischarge-Machinable Silicon Carbide Ceramics Sintered with Yttrium Nitrate

Abstract: A silicon carbide (SiC) powder compact was prepared with submicrometer β‐SiC, yttrium nitrate as a sintering additive, and polysiloxane‐phenol resin as precursors for nanosized SiC. By hot‐pressing, fully dense SiC ceramics with good electrical conductivity, as high as 3 × 104 (Ω·m)−1 at room temperature, were obtained. The ceramics could be machined to complex shapes by electrodischarge machining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 22 publications
(29 reference statements)
1
48
0
Order By: Relevance
“…The observed decrease in resistivity with decreasing temperature suggests a semiconductor-metal transition, 28 as observed in SiC sintered with YN. 19 Hall measurements at room temperature showed that the samples had n-type behaviour with carrier concentrations of 8.8 × 10 18 , 1.1 × 10 20 , 2.5 × 10 20 , and 2.6 × 10 20 cm −3 for 0Y, 3.1Y, 6.3Y, and 12.6Y, respectively. The carrier mobility of the 0Y, 3.1Y, 6.3Y, and 12.6Y samples was 1.8, 3.5, 4.9, and 4.8 cm 2 /(V s), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed decrease in resistivity with decreasing temperature suggests a semiconductor-metal transition, 28 as observed in SiC sintered with YN. 19 Hall measurements at room temperature showed that the samples had n-type behaviour with carrier concentrations of 8.8 × 10 18 , 1.1 × 10 20 , 2.5 × 10 20 , and 2.6 × 10 20 cm −3 for 0Y, 3.1Y, 6.3Y, and 12.6Y, respectively. The carrier mobility of the 0Y, 3.1Y, 6.3Y, and 12.6Y samples was 1.8, 3.5, 4.9, and 4.8 cm 2 /(V s), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Bulk SiC samples pressed under 40 MPa at 2050 • C for 6 h in nitrogen atmosphere exhibited electrical resistivity as low as 3 × 10 −3 cm at room temperature. 19 The YN-added SiC samples were found to contain a Y 2 O 3 phase segregated at the boundaries between SiC grains. During hot-pressing, YN reacts with SiO 2 , a native oxide in SiC particles, to form Y-Si-oxycarbonitride melt by the dissolution of SiC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 It is well known that Al substitutes for Si and N substitutes for C in the SiC lattice. 34,35 The solubility limit of AlN in 4H-SiC is ∼14 mol% at 2200 • C. 36 AlN was incorporated into the SiC grains, whereas the locations of the electrically insulating Nd-and Ho-containing phases were confined to the junctions with neighboring grains. Previous work 37 indicates that the Nd-and Ho-containing phases may be Nd 2 O 3 and Ho 2 O 3 , respectively, where the presence of Y 2 O 3 in the junction phase was identified when the content of a Y-containing additive was larger than that in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…From the electrical conduction viewpoint, SiC is a semiconductor with fairly large band gap energies ranging from ∼2.4 to 3.4 eV, depending on the structural polytype [4,5], thus exhibiting low electrical conductivity (σ) (close to 10 −13 S m −1 [6]). However, SiC-based ceramics can be tailored to display very diverse σ values within a range from 10 −9 to 10 5 S m −1 [6][7][8][9][10][11][12][13][14], depending on the type of doping, often resulting from sintering additives. In this sense, the case of sintering additives containing nitrogen (N) is especially significant, since N atoms can be incorporated into the SiC lattice substituting for carbon (C) during sintering [15], creating a donor level within the bandgap.…”
Section: Introductionmentioning
confidence: 99%